Features of the kinematics structure of ball throwing and catching techniques in rhythmic gymnastics at the stage of preliminary basic training - Natalia Olehivna Andreieva; Oleksandr Valeriiovych Zhyrnov; Yuriy Mykolayovych Salyamin (Kazimierz Wielki University, 2020)
The purpose of the research is to study the features of the kinematics structure of the technique on throwing and catching ball by athletes engaged in rhythmic gymnastics at the stage of preliminary basic training. Research methods include analysis and generalization of data received from scientific and methodical literature, video shooting, biomechanical video-computer analysis of movements, method of expert assessment, methods of mathematical statistics. The contingent under study accounts for 20 gymnasts of the second youth category aged 9-10. The peculiarities of the kinematics structure of motor actions of gymnasts when performing two basic sets of ball exercises, which are learned at the stage of preliminary basic training, were examined. Research results and their discussion. Quantitative information was obtained about the indicators of the kinematics structure of the nodal elements for sports technique, associated with basic set of ball exercises: from two or three steps - throwing the ball in the "Cossack" jump - catching into the roll on both hands and back in rhythmic steps; and from two or three steps - throwing the ball in a jump touching in the ring - catching into the roll on both hands and back in rhythmic steps. Based on the indicators of biomechanical analysis of the two basic sets of ball exercises performed, the phase structure of exercises is specified and the key elements of sports technique of throwing and catching the ball are studied. For a more detailed analysis in both studies, we selected three nodal elements: the starting pose of the body (the moment of releasing the ball), the multiplication of the body pose (body position during the jump) and the final body pose (the moment of catching the ball). Conclusion. Objective quantitative biomechanical information about indicators of kinematics structure of nodal elements for sport technique consisting of basic set of ball exercises is received: from two-three steps - throwing the ball in the "Cossack" jump - catching into the roll on both hands and back in rhythmic steps; and from two or three steps - throwing the ball in a jump touching in the ring - catching into the roll on both hands and back in rhythmic steps. The obtained characteristics of the kinematics structure of the nodal elements of throwing and catching the ball during both basic exercises, can be used as model indicators for more effective technical training of young gymnasts. Conflict of interest. The authors state that there is no conflict of interest. The prospect of further research is associated with development of the models of nodal elements motor structure, used as sport technique for exercises with objects at the stage of specialized basic training.